THE INFLUENCE OF CHANGES IN TECHNOLOGY AND ORGANIZATIONAL CULTURE ON INNOVATION PERFORMANCE THROUGH ORGANIZATIONAL (International Conference on Economics, Business, and Management Research (ICEBMR), 2023)
The purpose of this paper is to understanding the role change technology, culture organization enhance performance innovation and commitment organization as mediation. This paper will give understanding in a deep factor what variable increase performance innovation direct or trough mediation. This study used a quantitative approach. Primary data collection using survey methods. Survey is a measurement process used to collect data using questionnaires. The result show that role Change Technology and culture resulting organization _ from several reviews literature proven own influence positive to performance innovation, besides That commitment organization is also deep literature this is also affected by Change Technology and culture organization and also proven influence performance innovation. This thing becomes findings in study this and can become a conceptual research framework empirical.
Keywords: change technology; culture orgnization; commitment organization; performance innovation.